Optimasi Performa Kompor Oli Bekas dengan Variasi Jenis Bahan Bakar dan Sistem Preheating - Sudarno, Sudarno; Wahyuni, Nurul Sri; Ramatulloh, Arya Eka (Universitas Muhammadiyah Metro, 2025)
Previous studies have shown that used oil can be used as an alternative fuel, although its efficiency is relatively low with a red to orange flame. To improve performance, design improvements need to be made, namely by preheating the fuel before entering the combustion chamber, selecting the right fuel, and improving the distribution of combustion air. This study aims to find the effect of fuel type on the resulting performance. The study was conducted using analysis and experimental methods. In this study, we continued the investigation related to the effect of fuel type on the resulting performance. The types of fuel used were used cooking oil, used oil, and new oil. The performance measured included efficiency, flame temperature distribution, and exhaust emissions. Based on this study, it was found that the stove with new oil fuel produced the best performance with the highest efficiency value of 56,16%. The highest temperature produced by new oil reached 1094°C, indicating better thermal stability compared to other fuels. In addition, exhaust emission tests showed that new oil produced the highest CO₂ levels (10,0%), the lowest CO (2,24%), and the lowest HC (24,4 ppm), indicating the most perfect combustion. This confirms that the use of new oil in used oil stoves with fuel preheating can increase thermal efficiency, and produce cleaner emissions.